Analisis Kebijakan Pendidikan Full Day School di SD Islam Terpadu Al Anshar Tanjung Pura - Muhammad Iqbal; Aziza Rahmah; Wilianda Muthe; Restiana Harahap; Abdul Halim Siregar; Indri Sofia (Journal on Education, 2023)
Determination of full day school learning is a new policy that enforces learning at the Al-Ansar Tanjung Pura Integrated Islamic Elementary School all day long. Education which is dynamic in nature is of course always carrying out reforms in order to catch up with Indonesia's education with developed countries, especially at Al-Ansar Tanjung Pura Integrated Islamic Elementary School. However, this certainly requires careful preparation in order to minimize the emergence of conflict. Community concern arises because the existence of full day school is feared that it can damage the existing order, such as the teaching of madrasah diniyah. Of course this will have an impact on community empowerment and children. This research will discuss further about the product of policy formulation and the problems of implementing the full day school education system at Al-Ansar Tanjung Pura Integrated Islamic Elementary School. The method used is a literature study, and it results that education management cannot be separated from education policy because the two work in synergy with each other. Likewise, education and politics cannot be separated either. Both have an important role with the same goal of advancing the nation. The goals, direction, values ​​and education budget are not spared from the results of political agreements..